Efgartigimod Followed by Telitacicept in Adult Generalized Myasthenia Gravis: A Retrospective Case Series - Zhang Y; Fang Z; Liu Y; Wan B; Zhang Q; Qu X; Pan S; Zhang Y; Dai Y; Yang S; Li J; Zhang X (Journal of Inflammation Research)
Yuan Zhang,1,* Zheyu Fang,1,* Yaping Liu,2,* Bingbing Wan,1 Qiaoyi Zhang,1 Xi Qu,1 Shengli Pan,1 Yu Zhang,1 Yilin Dai,1 Shiyin Yang,1 Jia Li,1 Xu Zhang1 1Department of Neurology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 2Department of Neurology, Lianshui People’s Hospital, Huai’an, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jia Li, Email lijia@wzhospital.cn Xu Zhang, Email drzhangxu@live.cnBackground: The emergence of biologics for the treatment of generalized myasthenia gravis (gMG) has increased therapeutic options, but evidence on their flexible use remains limited.Purpose: This study retrospectively analyzed gMG patients treated with efgartigimod followed by telitacicept.Methods: A retrospective analysis was conducted on gMG patients treated with efgartigimod followed by telitacicept. Outcomes included changes in Quantitative Myasthenia Gravis (QMG) and Myasthenia Gravis-Activities of Daily Living (MG-ADL) scores from baseline to weeks 13 and 28, Minimal Manifestation Status (MMS), corticosteroid-sparing potential, safety, and serological markers.Results: Among seven patients included for efficacy evaluation, the baseline QMG and MG-ADL scores were 12.4± 4.3 and 7.1± 3.6, respectively. These scores decreased by 8.4± 3.9 and 5.7± 4.2 at week 13 and further decreased by 8.7± 3.2 and 6.8± 3.4 by week 28 (both P < 0.001). Six patients (86%) achieved Minimal Manifestation Status (MMS), with a median time to achieve MMS being 9 weeks. The average prednisone dosage was significantly reduced from 51.43± 14.64 mg at baseline to 5.71± 1.89 mg by week 28 (P < 0.05). Common adverse events included mild injection site reactions (n=2) and upper respiratory infections (n=2), with no serious events reported. IgM and IgA levels significantly declined by week 17 (P < 0.05), while BAFF levels increased significantly following telitacicept treatment by week 21 (P < 0.05).Conclusion: This regimen demonstrated favorable efficacy and safety, suggesting its potential as an effective option for gMG management.Keywords: generalized myasthenia gravis, efgartigimod, telitacicept, sequential therapy, targeted therapy